2012
DOI: 10.1016/j.eururo.2011.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Open and Minimally Invasive Partial Nephrectomy for Renal Tumors 4–7 Centimeters

Abstract: OPN and MIPN procedures performed in patients with tumors>4-7 cm offer acceptable and comparable results in terms of operative, functional, and convalescence measures, regardless of approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 38 publications
0
43
0
4
Order By: Relevance
“…At contrary, RPN seemed to be a more reproducible technique, able to bridge the technical difficulties of LPN in favor of a broader diffusion of minimally invasive PN. A few well-designed comparative studies have investigated the perioperative outcomes of RPN versus those of LPN [6][7][8], while to date no prospective studies comparing RPN and OPN are available, but only few retrospective series with limited cases [9][10][11]. The aim of the present study is to compare the perioperative results and surgical complications of RPN and OPN.…”
Section: Introductionmentioning
confidence: 99%
“…At contrary, RPN seemed to be a more reproducible technique, able to bridge the technical difficulties of LPN in favor of a broader diffusion of minimally invasive PN. A few well-designed comparative studies have investigated the perioperative outcomes of RPN versus those of LPN [6][7][8], while to date no prospective studies comparing RPN and OPN are available, but only few retrospective series with limited cases [9][10][11]. The aim of the present study is to compare the perioperative results and surgical complications of RPN and OPN.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 The understanding of increased risk of chronic kidney disease (CKD) with radical nephrectomy as well as recent data highlighting the association between CKD and cardiovascular morbidity and mortality have led to the desire to preserve as much normal renal parenchyma as possible. 6 Several factors are thought to impact postoperative renal function, including patient-related factors such as age, comorbidities, and preoperative renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Nephron-sparing surgery in multiple renal cancer: a case report for Adverse Events grading system [14]. Sprenkle et al reported complications rate of 13% approximately as well [15]. Sidana et al, in a sample of 162 patients undergone to PCA, LCA, or open CA, reported complication rates higher, up to 23.5% (complications were categorized using the Clavien-Dindo system).…”
Section: Discussionmentioning
confidence: 99%